PENDAMPINGAN OLEH BALAI PEMASYARAKATAN (BAPAS)KELAS II PURWOKERTO TERHADAP ANAK YANGMELAKUKAN KEKERASAN MENGAKIBATKAN MATINYAKORBAN(STUDI PUTUSAN NOMOR : 3/PID.SUS-ANAK/2021/PN.PBG) - Muhammad Rifaldi; Rahtami Susanti (Wijayakusuma Law Review, 2023)
Assistance by the Purwokerto Correctional Center for child perpetrators of RP (17 years) whocommitted violence resulting in the death of the victim was carried out from the Pre-adjudication,Adjudication, Post-adjudication stages in accordance with the provisions of Law number 11 of 2012concerning the Juvenile Criminal Justice System. This study aims to find out the assistance by thePurwokerto Correctional Center for children who committed violence resulting in the death of the victimin decision number 3/Pid.Sus-Anak/2021/PN.Pbg and the constraints of the Purwokerto CorrectionalCenter in assisting children which resulted in the death of the victim in decision number 3/Pid.SusChild/2021/PN.Pbg. The type of research used is empirical juridical with the main data source beingprimary data. The results of the research show that the Purwokerto Correctional Center has providedassistance since the RP was investigated at the police office, examination at trial until after the courtdecision. The obstacle faced by the Purwokerto Correctional Center in assisting RPs is the existence ofRPs which are difficult for assistants to reach because their houses are in mountainous areas wherecommunication facilities and road infrastructure are difficult for PKs to access.